Book Review Selling Destinations: Geography For The Travel Professional (Malaysian Management Journal, 2013)
Most undergraduate programmes in tourism management in Malaysia and elsewhere include a course on tourism geography. Knowledge of geography is deemed essential on the ground that it will equip travel and tourism professionals with geographic literacy of both the immediate environment at a particular destination and the world outside, regional and international. Travel counsellors, tourist guides and hotel guest contact personnel in particular, need knowledge in geography to be in the position to advise or provide visitor information on numerous geographic aspects of a destination such as weather, distance, time, location, direction, costs, terrain and the physical environment, especially fauna and flora. Mancini wrote Selling Destinations: Geography for the travel professional with this in mind. He begins the textbook with a debatable observation that travel professionals do not sell travel, what they really sell is geography. While it is true that most travellers see the burden of transfer from the place of origin to the destination as the less favored part of leisure travel, many travellers such as the early explorers, pilgrims, globetrotters and nowadays cruise ship passengers, value the transit experience as part of the leisure travel package. Indeed for the more exclusive niche markets such as space travel, overnight ecotourism hiking trails and mountain climbing, the thrill lies in the journey itself rather than any expected â€˜eurekaâ€™ at the destination. Travel is thus always an inseparable part of a tour package.The book is big and thick, not a user-friendly volume that readers can conveniently pass around or carry in the suitcase. The author tries to cover a long list of places and items, at the expense of useful foci on pertinent elements at the destination. As a result it paradoxically suffers a lack of both depth and breath. In terms of depth the text is hardly academically rigorous as it claims to be (p. vii). For a self-proclaimed bestseller textbook that is used in more than 60 travel schools in Canada the reader expects a list of references at the back of the book if not after each chapter. Unfortunately the author prefers to stray from the familiar by not including features that, he worries, may â€˜clutterâ€™ the mind and this includes distractive references. Selling Destinations... seems to be the only travel geography text in the market that strangely omits references to othersâ€™ works. Thus it claims without evidence that, â€œFifty-two percent of travellers pick the restaurant they will eat in before arriving at their destinationâ€ (p. 7), and that the word â€˜serendipityâ€™ comes from the Muslim name for Sri Lanka! In the same breadth this is hardly a scientific text which resorts to a tendentious myth (p. 583) that the eruption of Krakatoa in A. D. 535 caused...the rise of Islam (note: the religion of Islam was not founded until A. D. 622). It also claims that Jerusalem is the capital of Israel (p. 440) although this is still contestable.Coverage of the world is fairly comprehensive albeit uneven. For instance while Canada is allotted 72 pages, Malaysia, Indonesia, Philippines, Taiwan and Korea are only allocated one page each, notwithstanding the fact that Malaysia receives far more tourists that Canada. There is a conspicuous absence of Air Asia and Langkawi in the description of inbound airlines and island destinations in Malaysia. That the author refers to eastern Malaysia as Sarawak and Sabah regions rather than states indicates his own lack of geographic literacy. This book nonetheless offers the beginner an adequate descriptive framework which covers the essential geographic elements of a destination, namely location, local weather and climate, time zone, landscape, accessibility and key attractions. To Manciniâ€™s credit students will find the trivia, misgivings and quiz sections enjoyable. As the reader proceeds from continent to continent s/he will be increasingly familiar with a rather formulaic format which details information on how to get to the destination, local weather, tips on getting around, possible itineraries, allied destinations, factors that motivate visitors and sales considerations. The prospective visitor is also alerted to possible misgivings on the destination which the travel counsellor might want to address in his/her advice to the client.This is clearly a book on the geography for travel which aims at equipping students with the core competencies for travel counselling. It contrasts with the less vocational orientation of other tourism geography books which devote some space for the geography of tourism with its key concepts and theories. In the latter emphasis is usually given to explaining why tourists and facilities catering to their needs are concentrated in particular regions and locations. For an understanding of the distribution patterns Ullmanâ€™s model on spatial interaction and Butlerâ€™s idea on the evolution of a tourist destination are now common knowledge, as are concepts of tourism demand and supply, and more recently ideas on â€˜sustainable tourismâ€™. Although Mancini does not delve explicitly into the five themes associated with the above concepts: location, place, human-environment interaction, movement and the character of a region as the destination, the diligent learner would nevertheless be able to connect the dots by the end of the course. His use of side notes and trivia boxes helps to make reading a breezy and enjoyable task. The reader is also provided with a 6.5 cm margin to write whatever noteworthy comments s/he wants to write for future reference and recollection.Selling Destinations...is clearly tailor-made for Canadian undergraduates, hence the disproportionate emphasis on the geography of Canadian destinations. A titular subscript Geography for the Canadian Travel Professional would have been more appropriate given such an emphasis. In view of its vocational orientation one does not expect this expensive book, now in its fifth edition, to be included in scholarly reviews among geographers. It is ironic that such a successful book in the market receives no mention in any scholarly review in the subfields of tourism geography or tourism marketing. The author himself seems oblivious to the existence of a large and growing body of literature on tourism geography and destination marketing. There is thus still a lack of integration in tourism geography literature with one concentration addressing geography for tourism while the other on geography of tourism. For a more comprehensive treatment the two sections clearly ought to come together.